GC-MS Profile, Antioxidant Activity, and in Silico Study of the Essential Oil from Schinus molle L. Leaves in the Presence of Mosquito Juvenile Hormone-Binding Protein (mJHBP) from Aedes aegypti - Herrera-Calderon, Oscar (2022)
Schinus molle is a medicinal plant used as an anti-inflammatory and for rheumatic pain in the traditional medicine of Peru. On the other hand, Aedes aegypti is the main vector of several tropical diseases and the transmitter of yellow fever, chikungunya, malaria, dengue, and Zika virus. In this study, the aim was to investigate the antioxidant activity in vitro and the insecticidal activity in silico, in the presence of the mosquito juvenile hormone-binding protein (mJHBP) from Aedes aegypti, of the essential oil from S. molle leaves. The volatile phytochemicals were analyzed by gas chromatography-mass spectrometry (GC-MS), and the profile antioxidants were examined by DPPH, ABTS, and FRAP assays. The evaluation in silico was carried out on mJHBP (PDB: 5V13) with an insecticidal approach. The results revealed that EO presented as the main volatile components to alpha-phellandrene (32.68%), D-limonene (12.59%), and beta-phellandrene (12.24%). The antioxidant activity showed values for DPPH=11.42±0.08 μmol ET/g, ABTS=134.88±4.37 μmol ET/g, and FRAP=65.16±1.46 μmol ET/g. Regarding the insecticidal approach in silico, alpha-muurolene and gamma-cadinene had the best biding energy on mJHBP (ΔG=-9.7 kcal/mol), followed by beta-cadinene (ΔG=-9.5 kcal/mol). Additionally, the volatile components did not reveal antioxidant activity, and its potential insecticidal effect would be acting on mJHBP from A. aegypti.